Comparative Study of Growth Circle Patterns in Otoliths of Guppy Fish (Poecilia reticulata) from Areas Polluted with Domestic Sewage - Wulandary, Marchya Audhya; Putra, Ridwan Manda; Windarti, Windarti (Fakultas Perikanan dan Kelautan Universitas Riau, 2025)
Guppy fish (Poecilia reticulata) inhabit polluted water, such as domestic waste-filled ditches in residential areas, as well as in rivers. These two habitats have different water qualities, which affects the growth of the fish; this is reflected in the pattern of growth rings in the otoliths. To determine the differences in growth ring patterns of otoliths in guppies living in ditches versus the river, a study was conducted in March and April 2025. Fish were caught using a scoop net once every 2 weeks, three times. The fish were measured, and otoliths were taken. They were then attached to objects made of glass and manually shaved using a smooth grindstone. The growth rings in the otolith were observed using a microscope. Results showed that 103 fish were caught, 50 from the trench and 53 from Tangkerang River. The size of the fish caught was 18-31 mm from the trench and 17-31 mm from the river. In fish with the same total length, the otoliths from the river were longer and wider (0.5-1 mm in length and 0.4-0.95 mm in width), whereas those from the trench were shorter (0.42-0.85 mm in length and 0.4-0.67 mm in width). The maximum number of dark rings on the otoliths of fish from the ditch was 3, whereas from the river, it was 4. There were 27 fish from the river and 18 fish from the trench that had no dark ring in the otolith. The data obtained show that the growth of guppies in the Tangkerang River is better than in the Purigiam Housing trench